Mr. Topaze Based on a Play by Marcel Pagnol - Pagnol, Marcel (BFI, 2019)
Peter Seller's debut as a director is a rather lyrical bittersweet 1960s version of a Marcel Pagnol play adapted for the screen by Pierre Rouve with wit and insight. Playing the lead with a drôle debonair melancholy, Sellers is a well-meaning provincial teacher desperate to do the right thing and marry his love Ernestine. He prides himself on his integrity but puts his foot down at giving higher marks to the grandson of a wealthy baroness (Martita Hunt). He is fired as a result, and then led astray by Herbert Lom's snide and corrupt government official, Castel Benac, who with his mistress and actress Suzy intend to set up a dodgy financial business using Topaze as the malleable managing director. The moral of the tale is that money is power. And Topaze eventually discovers this. [filmuforia.co.uk]
Keywords: Blu-Ray-Disc